IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Norzawani Abd Talib - Abd Talib, Norzawani (2015)
Article on: Article 1 - “Audiovisual Materials in UK Public Libraries Economic Sense” Article 2 - “Audiovisual Production Restoration Archiving and Content Management Methods to Preserve Local Tradition and Folkloric Heritage”